Exploring Best SHRM Practices-Trust Relationship: An Empirical Approach - Al Adresi, Alaeldeen Saleh; Mohd Ridzuan, Darun (AGBA, 2015)
In the economic realities, organizations are constantly changing forcefully due to the pressure of controlling costs by reducing staffs or by asking employees to deliver more with less. Organizations need employees who are willing to contribute beyond their job description. It is the challenge for the organization to deal with the internal capabilities to cope up with the external turbulence. For some time human resource management is reported to have assumed greater importance within organisations (Legge, 1995; Nankervis and Debrah, 1995).